Batch and column tests for the development of an immobilization technology for toxic heavy metals in contaminated soils of closed mines - Jang, A; Choi, YS; Kim, IS (PERGAMON-ELSEVIER SCIENCE LTD, 1998)
Laboratory tests of various chemical treatments for the immobilization of copper, nickel, and lead in soils typically found at mine facilities were evaluated. A series of batch, adsorption tests, and lab-scale continuous column tests were conducted to optimize the design parameters for the full-scale immobilization processes. The laboratory test program consisted of batch and column experiments to measure the leachability and subsequent immobilization of the single heavy metal, Cu2+, Pb2+, and Ni2+ in an artificial soil which was composed of bentonite and quartz fine sand. Batch equilibrium methods were used to test the ability of a large number of chemical additives to react with heavy metals in contaminated soil. The two best treatment chemicals (CaO and Na2S) for each soil-metal combination were selected for more detailed columns studies. The column rests were carried out in the acidic pH range. According to the results of the column leaching test, it was found that the degree of heavy metal leaching is highly dependent on pH. An adsorption test was performed under acidic conditions (pH 4) to evaluate bentonite as an additive to treat acid mine drainage (AMD). (C) 1998 IAWQ. Published by Elsevier Science Ltd.